A perspective on restoration with foundation plants across anthropogenic dry forests of the Southern Cone and the Sahel - Root-Bernstein, Meredith; Addo-Danso, Shalom D.; Bestelmeyer, Brandon (Frontiers in Ecology and Evolution, 2024)
Rewilding is a flexible conservation approach that may be applicable to a wide variety of ecological, historical and socio-cultural contexts. We believe that comparative socio-ecological research on woodland habitat trajectories among contexts is an excellent opportunity to consider possible rewilding approaches. Here, we draw on a comparison between arid and seasonally dry woodlands of the Sahel region of Africa and the Southern Cone of South America. The two regions, while sharing a common Gondwanan floral origin, differ in terms of subsequent biogeographical processes and have different climatic gradients. Historically, both regions were colonised, although along different models, and the Southern Cone has experienced greater land-use change and agricultural modernisation. Culturally, both regions have indigenous populations with traditional management techniques and local ecological knowledge, although attention to these topics in research and conservation has had different emphases in each region. Rewilding, focusing on charismatic animals, has been proposed and implemented in some parts of the Southern Cone, but has hardly been mentioned for the Sahel. We discuss the applicability of potential rewilding models involving key plants for each region, and what a plant-focused rewilding practice could gain from a comparative approach in the two regions.